Risk assessment of the common air pollutants in Teplice, Czech Republic - Cerná, M; Jelínek, R; Janoutová, J; Kotesovec, F; Benes, I; Leixner, M (Toxicology letters, 1998)
In the framework of the systematic investigation of the environment of the district of Teplice (Northern Bohemia), one of the most polluted regions in Europe, an attempt was made to estimate health risks to the inhabitants posed by the most common air contaminants (SO2, NOx, particulate matter). A meta-analysis of data published in recent papers dealing with health effects was performed. At first we weighed the number of positive and negative findings focusing on the following health indicators: prevalence of symptoms (coughing, wheezing), decreased respiratory function, prevalence of respiratory illness, and acute mortality. Only those categories in which the positive findings prevailed were taken into consideration and median values for LOAELs were calculated from the data referring to positive dose-response relationships. The exposure assessment was based upon a series of data on daily concentrations of the air contaminants in Teplice since 1975. Due to the somatic and respiration parameters, as well as to their habits, children between the ages of 8 and 10 appeared the most heavily exposed of all age groups. It was concluded that in real concentrations the risk is posed mainly from sulphur dioxide and, above all, from particulate matter.
Keywords: dospělí; velikost částic; hodnocení rizik; Female; Infant; dítě; předškolní dítě; novorozenec; Adult; oxidy dusíku; ženské pohlaví; Particle Size; oxid siřičitý; Adolescent; lidé; Infant, Newborn; Risk Assessment; Male; Air Pollutants; kojenec; Czech Republic; Child, Preschool; vystavení vlivu životního prostředí; Česká republika; Child; mužské pohlaví; látky znečišťující vzduch; Environmental Exposure; Nitrogen Oxides; mladiství; Sulfur Dioxide; Humans